Modeling of bubble column slurry reactor for reductive alkylation of p-phenylenediamine - Chaudhari, Amit S.; Rampure, Mohan R.; Ranade, Vivek V.; Jaganathan, Rengaswamy; Chaudhari, Raghunath V. (Chemical Engineering Science, 2007)
A bubble column slurry reactor (BCSR) model has been developed for the reductive alkylation of p-phenylenediamine (PPDA) with methyl ethyl ketone (MEK) to N, N'-di-secondary-alkyl-p-phenylenediamine (Di-amine). This particular reaction system is commercially relevant and involves a combination of parallel and consecutive reactions comprising equilibrium non-catalytic (homogeneous) and catalytic (heterogeneous) steps. The proposed model is based on the `mixing cell approach'. In this work the mixing cell approach has been extended by including a liquid backflow stream from all but the bottommost mixing cell. The model incorporates the contributions of gas-liquid and liquid-solid mass transfer, heat effects, and complex multistep reaction kinetics. CFD model is used to estimate the extent of backflow among mixing cells and its dependence on operating parameters. The effect of gas and liquid velocities, catalyst loading, inlet PPDA concentration, and temperature on the conversion, selectivity, global rate of hydrogenation, and temperature rise is discussed. The comparison of the current approach with the traditional mixing cell model is discussed. The BCSR model presented here will be useful to provide guidelines for designing and improving overall performance of bubble column reactors. (C) 2007 Elsevier Ltd. All rights reserved.
8th International Conference on Gas-Liquid and Gas-Liquid-Solid Reactor Engineering, Indian Inst Technol Delhi, New Delhi, INDIA, DEC 16-19, 2007
Keywords: bubble columns; CFD; kinetics; Mathematical modeling; Reductive alkylation

Mathematical modeling and simulation of bubble column reactor for aerial liquid phase cyclohexane oxidation - Upkare, Makarand M.; Rajurkar, Kalpendra B.; Gupta, Pankaj R.; Jaganathan, Rengaswamy (International Conference on Modeling, Optimization, and Computing, 2010)
Cyclohexane oxidation is an important but complex commercial reaction, wherein the desired product, K-A oil appears as an intermediates of the reaction sequence. A mathematical model has been developed for the bubble column reactor operating under isothermal conditions. The mass and energy model equations consisted of stiff ODEs. The model was applied to describe the behavior of bubble column reactor for aerial liquid phase cyclohexane oxidation. Effect of initial substrate concentration, catalyst loading and temperature was studied and discussed in detail. Conclusions were presented at the end of the study.
International Conference on Modeling, Optimization, and Computing, Durgapur, INDIA, OCT 28-30, 2010
Keywords: K-A Oil Selectivity; Mathematical modeling; substrate conversion and product yield analysis